In-Vitro Screening Of Mucuna Pruriens Seeds Extract For Antilice Activity - SINGH DINESH,; GARG GOPAL,; GUPTA VISHAL, (International Journal of Pharma and Bio Sciences, 2011)
Pediculus humanus capitis, otherwise called as the human head louse, infestation is a major concern in public health associated problem. Resistance of pediculocidal drug towards head louse laid the foundation for research in exploring noval antilice agents from medicinal plants. In present study, various extracts of Mucuna pruriens seeds were tested against the head louse Pediculus humanus capitis. A simple method was conducted for determining the potential pediculocidal activity of ethyl acetate, petroleum ether and water extracts of Mucuna pruriens seeds. The finding revealed that petroleum ether extracts possess excellent antilice activity where as ethyl acetate showed moderate pediculocidal effects. Water extract was devoid of pediculocidal activities. All the results were well comparable with benzoyl benzoate (25%w/v). These results showed the prospect of using Mucuna pruriens seed extracts a against Pediculus humanus capitis in difficult situations of emergence of resistance to synthetic anti-lice agents.